POWER OF THE TESTS DENGAN NON-SAMPLE PRIOR INFORMATION PADA PENGUJIAN HIPOTESIS SATU ARAH - Budi Pratikno; Lina Sulistia; Yuliatri Wirawidya Haryono (Universitas Jenderal Soedirman, 2016)
The research discussed power of the tests with non-sample prior information (NSPI) in testing intercept on one-side-hypothesis. The testing is condcuted on a simple regression model (SRM) and multivariate simple regression model (MSRM), and the power of the tests are unrestricted test (UT), restricted test (RT), and preliminary-test test (PTT). The method for choosing the best tests is a maximum power and minimum size. A simulation study and graphical analysis are given using generate and real data. The result showed that the power of the test of the PTT are an alternative choice among the tests on both SRM and MSRM.